1996
DOI: 10.1210/jcem.81.3.8772580
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of the human amylin analog AC137 on basal and insulin-stimulated euglycemic and hypoglycemic fuel metabolism in patients with insulin-dependent diabetes mellitus.

Abstract: Amylin has been reported to decrease glycogen storage in rodent skeletal muscles and produce insulin resistance in intact rats. To test the acute effect of a human amylin analog (AC137) on glucose metabolism in man, seven IDDM patients were infused in a randomized, double blind, cross-over study with AC137 (100 micrograms/h, n = 1; 50 micrograms/h, n = 6) or placebo for 330 min during a two-step euglycemic clamp (insulin infusion rates, 0.2 and 0.6 mU/kg.min; basal and hyperinsulinemic period, respectively) fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 34 publications
5
22
1
Order By: Relevance
“…Chmielowska et al (2005) demonstrated that amylin administered centrally and peripherally produced a significant decrease in prolactin release in rats. Together, our results show that the interactions between plasma amylin and prolactin, a reproductive hormone, in goat neonates are not consistent with the findings in rats (Nyholm et al 1996). The observed differences between rats and goat neonates may be due to distinct receptor subtypes of amylin in each species.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Chmielowska et al (2005) demonstrated that amylin administered centrally and peripherally produced a significant decrease in prolactin release in rats. Together, our results show that the interactions between plasma amylin and prolactin, a reproductive hormone, in goat neonates are not consistent with the findings in rats (Nyholm et al 1996). The observed differences between rats and goat neonates may be due to distinct receptor subtypes of amylin in each species.…”
Section: Discussioncontrasting
confidence: 82%
“…Nyholm et al (1996) showed that amylin analogue AC 137 caused an increase in circulating cortisol during hypoglycaemia in patients with insulin-dependent diabetes mellitus. Our data suggest that the interactions between plasma amylin and cortisol, a metabolic hormone, in goat neonates are consistent with those observed with the amylin analogue in humans.…”
Section: Discussionmentioning
confidence: 99%
“…A similar observation was also made in insulin-treated type 2 diabetic patients (45). There is no evidence of an effect of pramlintide administration on insulin sensitivity in either peripheral tissues or the liver in type 1 diabetic patients (46), which reiterates the observations made in healthy individuals using native amylin (34) and which is further supported indirectly using an amylin antagonist (47) in obese type 2 diabetic and nondiabetic individuals. The latter study also demonstrated that the amylin antagonist was able to increase insulin secretion in lean and obese individuals, suggesting a possible physiological role of amylin to restrain insulin secretion.…”
Section: Pramlintide Studies In Diabetic Individualssupporting
confidence: 67%
“…The mechanisms underlying the lack of increase in severe hypoglycemia with pramlintide are not yet fully established but may involve an increase in liver glycogen stores (21), a reduction in diurnal glucose fluctuations (22), and/or an improved hormonal counter-regulatory response to hypoglycemia (23). Of note, both preclinical studies (24,25) and studies in patients with type 1 diabetes (26) indicate that the effects of pramlintide on gastric emptying and glucagon secretion are overcome in the presence of insulin-induced hypoglycemia. Although pramlintide itself does not cause hypoglycemia, even at high Data are % or means Ϯ SEM.…”
Section: Open-label Extension (Weeks 52-104)mentioning
confidence: 99%